Removal of hexavalent chromium by using heat-activated bauxite - Erdem, Mehmet; Altundoğan, Hamdi Soner; Tümen, Fikret (My University, 2004)
In this study, to increase the Cr(VI) adsorption capacity of bauxite, heat treatment method was tested and the effects of pH, adsorbent dosage, contact time, initial Cr(VI) concentration and temperature on the adsorption of Cr(VI) were investigated. Although heating provides an enhanced adsorption, the heat-activated bauxite was found to be a weak adsorbent for Cr(VI). The maximum adsorption yield (64.9%) was obtained at the conditions of pH 2, activated bauxite dosage of 20 g l?1, contact time of 180 min, for the initial Cr(VI) concentration of 10 mg l?1 and temperature of 20 °C by using the bauxite sample heated at 600 °C. The adsorption data fit a first-order rate expression and Langmuir isotherm. Enthalpy, free energy and entropy changes were calculated from the isotherm data. The adsorption of Cr(VI) onto heat-activated bauxite was found to be exothermic.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Environmental; Pollution; Oxide ores; Ion exchange